Implementación del sistema de evaluación del aprendizaje en la Institución Educativa San Felipe Neri, de Cartagena de Indias: estudio de caso. - Batista Álvarez, Allens (Educación, Ciencias Humanas y Sociales, 2018)
Learning evaluation is a much relevant topic when aiming to get high standards for quality of education. However, a review of Colombian situation shows that many public policies have been designed in order to achieve quality with participation of evaluation systems in schools. These institutional evaluation systems are meant to be designed according to the needs that are present on the context where schools exist. However, progresses does not comply with This research is designed as a study case in order to determine how these public policies are being implemented in the Educative Institution San Felipe Neri, specifically the 1290 Decree stablished in 2009. This approach contained document analysis, surveys and focus group, and according to the results, the global analysis detected improvement opportunities in the organizational processes that interfere with the design and implementation of the Institutional Evaluation System (SIE) in the classrooms.